Uncommon Association of Mckittrick-Wheelock Syndrome and Clostridioides difficile Infection in Acute Renal Failure - Irina Ciortescu (Diagnostics, 2022)
We present the case of a 71-year-old male who suffered an episode of acute renal failure caused by the uncommon association of two different diseases (Clostridioides difficile infection and McKittrick-Wheelock syndrome). He presented with hypovolemic shock, severe hypokalemia, hyponatremia, metabolic acidosis and acute renal failure; consequences of secretory diarrhea caused by a giant rectal tumor revealed from colonoscopy. The biopsy results revealed tubulo-villous adenoma with low/high grade dysplasia. After correction of electrolyte imbalances and azotemia, the patient underwent surgical resection with full subsequent recovery. In the literature review, including papers published from which January 1945 to April 2021, we found only one case-report of acute renal failure associated with Clostridioides difficile infection and McKittrick-Wheelock syndrome.